Efeito antinociceptivo do acetato de hecogenina em camundongos participação do sistema opióide - Quintans, Jullyana de Souza Siqueira (2013)
Hecogenin acetate (HA) is a steroidal sapogenin-acetylated, one of the most important precursor used by the pharmaceutical industry for the synthesis of steroid hormones. However, no studies were found on the possible analgesic profile of HA. Thus, we aimed to evaluate antinociceptive profile of HA in chronic and acute animal models. Acute pretreatment with HA (5 40 mg/kg) produced a dose dependent increase in the tail flick latency time when compared to vehicle-treated group (p<0.01) demonstrating central analgesic effect. The antinociceptive effect of HA (40 mg/kg) was prevented by naloxone (a non selective opioid receptor antagonist; 5 mg/kg), CTOP (μ opioid receptor antagonist; 1 mg/kg), nor- BNI (k opioid receptor antagonist; 0.5 mg/kg), naltrindole (δ opioid receptor antagonist; 3 mg/kg), or glibenclamide (ATP sensitive K+ channel blocker; 2 mg/kg). This effect no seems to be related to a possible myorelaxing profile of HA, since mice treated with HA (5 - 40 mg/kg) did not show motor performance alterations. Systemic administration of HA (5 - 40 mg/kg), increased the number of Fos positive cells in the periaqueductal gray and the acute pretreatment with HA, at all doses tested, significantly inhibited the Fos expression in the spinal cord dorsal horn. Additionally, intraperitoneal administration of HA (5, 10, or 20 mg/kg; i.p.) inhibited the development of mechanical hyperalgesia induced by carrageenan, TNF-α, dopamine and PGE2 in mice. When we investigated effects of HA (20 or 40 mg/kg, i.p.) on chronic neuropathic hypersensitivity (partial sciatic nerve ligation - PSNL), the acute treatment with HA was effective in producing a significanty (p<0.01) anti-hyperalgesic effect in PSNL model on mice. So, the present study demonstrates, for the first time, that HA produced consistent antinociception mediated by opioid receptors and endogenous analgesic mechanisms and that this compound may be useful in the study of new therapeutic approaches to pain treatment.